Missing in action - Perera, Suvendrini (Borderlands, 2012)
This essay weaves itself around the figure of the hip-hop artist M.I.A. Its driving questions are about the impossible choices and willed identifications of a dirty war and the forms of media, cultural politics and creativity they engender; their inescapable traces and unaccountable hauntings and returns in diasporic lives. In particular, the essay focuses on M.I.A.’s practice of an embodied poetics that expresses the contradictory affective and political investments, shifting positionalities and conflicting solidarities of diaspora lives enmeshed in war.